A fuzzy function granular - Abha Tripathi, Abha Tripathi; S.P. Tiwari, S.P. Tiwari; Kavikumar Jacob, Kavikumar Jacob; D. Nagarajan, D. Nagarajan (Elsevier, 2023)
This study introduces the concept of granular F-transform and investigates its basic properties using the theory of fuzzy numbers and horizontal membership functions. We further present a numerical method based on granular F-transform to solve a fuzzy prey–predator model consisting of two prey and one predator due to its natural variability and investigate the existence of the equilibrium points and their stability